Astragalus-Containing Chinese Herbal Medicine Combined With Chemotherapy for Cervical Cancer: A Systematic Review and Meta-Analysis - Shen, Lei; Gwak, Si Ra; Cui, Zhen Yang; Joo, Jong Cheon; Park, Soo Jung (Frontiers in Pharmacology, 2021)
Background: Cervical cancer is the fourth most common malignant tumor among women worldwide. This study aimed to evaluate the efficacy of Astragalus-containing Chinese herbal medicine (CHM) combined with chemotherapy (CT) for the treatment of cervical cancer. Methods: Ten electronic databases including PubMed, Cochrane library, Embase, Korean databases, and Chinese medical databases were systematically searched up to July 2020. All randomized controlled trials using Astragalus-containing CHM combined with CT to treat cervical cancer were included. Results: A total of 19 trials were included in the analysis. Compared with the control group, the Astragalus-containing CHM combined with CT group showed a significantly increased tumor response (complete and partial response) (risk ratio [RR] = 1.25, 95% confidence interval [CI]: 1.17–1.33, p < 0.00001) and Karnofsky performance score (KPS) (standardized mean difference [SMD] = 1.81, 95% CI: 1.46–2.17, p < 0.00001). This group also displayed remarkably reduced CT toxicity. Conclusions: Our study suggests that Astragalus-containing CHM might be a potential option for cervical cancer to enhance the curative efficacy and reduce CT toxicity.